Morphofunctional characteristics of magnocellular nuclei of hypothalamus in spontaneously hypertensive rats - Hliva, O.; Хлівна, А. Ю. (Чернівці, 2017)
Hypothalamus, particularly its paraventricular (PVN) and supraoptic (SON) nuclei, considered as a key element in the central mechanisms of blood pressure regulation. SON mostly involved in blood volume regulation, whereas PVN influences the lower cardiovascular centers in brain stem and spinal cord. We believe that it's necessary to study deeply the particular roles of these nuclei and their neuropeptides in hypertension pathogenesis.